Devolving Power and Decentralising Local Governance in Zimbabwe: Prospects and Impediments - Bvirindi, Jeremiah; Chikwawawa, Cosmas (Innovations in Science and Technology Vol. 8, 2022)
In an effort to ensure democracy, good local governance and citizen participation, chapter 14, section 264 of the Constitution of Zimbabwe Amendment (No.20) Act 2013 provides for devolution of government powers and responsibilities to provincial and metropolitan councils and local authorities. To facilitate devolution, the Constitution organizes government at three levels namely, national, provincial and local. However, contrary to the provisions of section 264 of the constitution the government has not given powers of local governance to the people to enhance their participation in making decisions affecting them. This paper discusses the objectives of the devolution of governmental powers and responsibilities, the prospects of improving good local governance through devolution and impediments to the implementation of devolution. The objectives of this study were to examine the extent to which the implementation of devolution and decentralization improved good local governance and to analyse the constitutional provisions as well as dynamics attendant to their implementation.